2015
DOI: 10.1016/j.legalmed.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA typing as a positive identification method for soft and hard tissues immersed in strong acids

Abstract: a b s t r a c tIdentification of human remains can be hindered by several factors (e.g., traumatic mutilation, carbonization or decomposition). Moreover, in some criminal cases, offenders may purposely adopt various expedients to thwart the victim's identification, including the dissolution of body tissues by the use of corrosive reagents, as repeatedly reported in the past for mafia-related murders.By means of an animal model, namely porcine samples, we evaluated standard DNA typing as a method for identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…S7). The artificial gastric fluid is a strong acid and has the potential to cause DNA fragmentation 31 . Short amplicons of the primer set such as ArA_ndhA primer (100 bp) could be successful for detecting simulated gastric samples even with 6 h digestion times.…”
Section: Resultsmentioning
confidence: 99%
“…S7). The artificial gastric fluid is a strong acid and has the potential to cause DNA fragmentation 31 . Short amplicons of the primer set such as ArA_ndhA primer (100 bp) could be successful for detecting simulated gastric samples even with 6 h digestion times.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the developed ITS2‐HRM assay can detect DNA from artificially digested samples in artificial gastric juice with high confidence. The artificial gastric fluid is a strong acid and has the potential to cause DNA fragmentation (Robino et al., 2015). More specifically, digestion in the artificial gastric juice after 0 and 1 h did not seem to have any significant effects on the detection of the toxic plant species in the simulated mixtures, indicated by the observed similarities among the melting curve profiles of both species (Figures 2 and 3), despite the observed DNA degradation after 1 h of digestion (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…A complete DNA profile was obtained from only one molar. The efficiency of DNA typing from teeth subjected to various experimental conditions, such as treatment with acids [49] and fire exposure [50,51], has been reported in the literature. In addition, the effect of the duration of the postmortem and postextraction periods in obtaining genetic profiles from the teeth has been analyzed [52,53].…”
Section: Discussionmentioning
confidence: 99%